Aplikasi Manajemen Jaringan Berbasis Software Defined Networking - Epaphras Ericson Thomas; Henry Palit; Agustinus Noertjahyana (Jurnal Infra, 2018)
In a large corporation with multiple network devices, a network operator often has to manually configure each device. However, there are some requirements to re-organize devices becomes more flexible in order to respond to challenges such as restricting host and port (services) access.SDN or Software Defined Network is believed by some people to be one solution to answer the above challenges. In this study, some of the above problems will be answered using the concept of SDN. If there is a point of management, it will be possible to change network behavior and / or other configurations, and make other changes dynamically or automatically (programmed), especially in policy changes. In this exploration, OpenWRT is embedded in network devices so it is possible to be controlled. To facilitate the programming of the network, then built web services that are equipped with security authorization.The results of this exploration show that the concept of Software Defined Networking can answer the above problems, with relatively low cost.